1997
DOI: 10.1111/j.1439-0523.1997.tb00976.x
|View full text |Cite
|
Sign up to set email alerts
|

Heritability estimates of field resistance to spot blotch in four spring wheat crosses

Abstract: Spot blotch of wheat {Triticum aestivum L.), caused by Bipolaris sorokiniana (Sacc. in Sorok.) Shoem., is a major disease m South Asia. Popular commercial cultivars have low levels of resistance to spot blotch. Information on the inheritance of spot blotch resistance in wheat is lacking. Field studies were conducted in four wheat crosses, each involving a Chinese hexaploid parent with high levels of resistance and a commercial cultivar with low to intermediate levels of resistance to spot blotch. Data were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 7 publications
9
22
0
Order By: Relevance
“…Pair-wise correlation coefficients between AUDPC and various agronomic traits were not consistent across the early-and late-heading groups of genotypes, except for DH and DM (Table 4).AUDPC was always negatively correlated with DH and DM. This shows that HLB severity is positively associated with earliness in wheat and supports the general observation among wheat scientists in South Asia that a genetic correlation exists between disease severity and earliness, making it difficult to combine early heading and HLB resistance (Duveiller & Gilchrist, 1994;Sharma et al, 1997b;Dubin et al, 1998;Duveiller et al, 1998). However, two recent studies have shown that HLB resistance and maturity are independently inherited (Sharma & Bhatta, 1999;Joshi et al, 2002), which suggests that selection for both these traits should be possible.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Pair-wise correlation coefficients between AUDPC and various agronomic traits were not consistent across the early-and late-heading groups of genotypes, except for DH and DM (Table 4).AUDPC was always negatively correlated with DH and DM. This shows that HLB severity is positively associated with earliness in wheat and supports the general observation among wheat scientists in South Asia that a genetic correlation exists between disease severity and earliness, making it difficult to combine early heading and HLB resistance (Duveiller & Gilchrist, 1994;Sharma et al, 1997b;Dubin et al, 1998;Duveiller et al, 1998). However, two recent studies have shown that HLB resistance and maturity are independently inherited (Sharma & Bhatta, 1999;Joshi et al, 2002), which suggests that selection for both these traits should be possible.…”
Section: Resultssupporting
confidence: 76%
“…The lack of a significant correlation between AUDPC and plant height supports the previous finding by Joshi et al (2002) that resistance to spot blotch and plant height in wheat were independent. Sharma et al (1997b) and Dubin et al (1998) also reported a weak association between height and foliar blight severity. Our findings indicate that it could be possible to combine shorter plant height with HLB resistance which was also present in a few genotypes included in this study (Table 3).…”
Section: Resultsmentioning
confidence: 87%
“…Shoem (syn. Helminthosporium sativum, teleomorph Cochliobolous sativus) is also considered an important disease in the eastern part of South Asia (Sharma et al 1997;Saari 1998;Pandey et al 2005;Siddique et al 2006;Joshi et al , 2007b. These countries are also getting support through regional nurseries and trials being organized by CIMMYT South Asia, Nepal out of which Eastern Gangetic Plains Screening Nursery (EGPSN) and Eastern Gangetic Plains Yield trial (EGPYT) have been proved very eVective in providing superior sources of resistance for spot blotch (Joshi et al 2007c).…”
Section: Biotic Stressesmentioning
confidence: 97%
“…Srivastava et al (1971) reported that seedling resistance to spot blotch was controlled by two dominant epistatic genes. Similarly, Sharma and Bhatta (1999a) found that three dominant epistatic genes were involved in the genetic control of spot blotch. In a field study in Mexico, Velazquez (1994) reported that spot blotch resistance was partially dominant, with two to three genes conditioning adult plant resistance.…”
Section: Introductionmentioning
confidence: 96%